Efficient and recyclable novel Ni‐based metal–organic framework nanostructure as catalyst for the cascade reaction of alcohol oxidation–Knoevenagel condensation. (4th October 2017) - Aryanejad, Sima; Bagherzade, Ghodsieh; Farrokhi, Alireza
Abstract : A novel Ni‐based metal–organic framework (Ni‐MOF) with a Schiff base ligand as an organic linker, Ni3 (bdda)2 (OAc)2 ⋅6H2 O (H2 bdda = 4, 4′‐[benzene‐1, 4‐diylbis(methylylidenenitrilo)]dibenzoic acid), was synthesized and characterized using powder X‐ray powder diffraction, thermogravimetric analysis, Brunauer–Emmett–Teller measurements, inductively coupled plasma atomic emission spectroscopy, transmission electron microscopy, elemental analysis and Fourier transform infrared spectroscopy. The synthesized Ni‐MOF exhibited a high catalytic activity in benzyl alcohol oxidation using tert ‐butyl hydroperoxide under solvent‐free conditions. Also, the efficiency of the catalyst was investigated in the cascade reaction of oxidation–Knoevanagel condensation under mild conditions. The Ni‐MOF catalyst could be recovered and reused four times without significant reduction in its catalytic activity. Abstract : A novel and well characterized nano Ni‐MOF with a Schiff base ligand was prepared. The Ni‐MOF has been applied as efficient catalyst in the cascade reaction of oxidation–Knoevanagel condensation under mild conditions.